Characterization of mRNA dysfunctional mechanisms associated with the genetic disease cystic fibrosis - Felício, Verónica Manuela Rôxo (2019)
Tese de doutoramento, Bioquímica (Genética Molecular), Universidade de Lisboa, Faculdade de Ciências, 2018